Ligand Free One-Pot Synthesis of Pyrano[2,3-c]pyrazoles in Water Extract of Banana Peel (WEB): A Green Chemistry Approach - Dwivedi, Kartikey Dhar; Borah, Biplob; Chowhan, L. Raju (Frontiers in Chemistry, 2020)
Here, we have developed a novel, simple, efficient, and green protocol for one-pot synthesis of pyrano[2,3-c]pyrazole using arylidene malononitrile and pyrazolone in Water Extract of Banana Peels (WEB) as a reaction medium at room temperature (r.t.). This is a green and general synthetic protocol without utilization of any toxic organic solvent, ligand, base that could be applicable for the wide substrate scope in good to excellent yields. This protocol has various advantages such as fast reactions, eco-friendly reaction conditions, easy isolation of the product without using column chromatography. The green chemistry matrices calculation like atom economy reaction, environmental factor, as well as process mass intensity indicates the eco-friendly nature of the protocol.